(untitled) (Ustozlar uchun, 2024)
Abstract: the purpose of this article is to demonstrate the trends in the development of methods of teaching foreign languages among humans. Moreover, you will be give information about pros and cons of using modern technology. Finally, there can be a variety of tips to learn foreign languages quickly.